2020
DOI: 10.3390/agronomy10070996
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Nutritional Characterization of Winemaking Lees: A New Food Ingredient

Abstract: Wine lees are defined as the sediment formed at the bottom of the tank or barrel after wine alcoholic fermentation. They have a heterogeneous composition and currently constitute 6% of the byproducts generated by each ton of wine grapes. However, it is the most under-researched of all the byproducts of the winemaking process. Therefore, with the aim of highlighting this byproduct, a physicochemical and nutritional characterization of winemaking lees from three different wine making processes (white, rosé, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
3
7
0
2
Order By: Relevance
“…There are some studies related to FAs of agri-food by-products such as grape by-products (e.g., pomace, stems, bunch) [25,31] and BSG [26,27,37]. Nevertheless, few studies have been reported related to FAs in wine lees [38] and potato peels [39], and as far as we know, no studies were performed using carrot peels. Therefore, the present study aims to evaluate the FAs profile of different agri-food byproducts, namely grape pomace, grape stems, grape bunches, white less, red lees, BSG, carrot, and potato peels using chromatographic and spectrometric approaches, as a strategy to evaluate its potential application for food-based matrices enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies related to FAs of agri-food by-products such as grape by-products (e.g., pomace, stems, bunch) [25,31] and BSG [26,27,37]. Nevertheless, few studies have been reported related to FAs in wine lees [38] and potato peels [39], and as far as we know, no studies were performed using carrot peels. Therefore, the present study aims to evaluate the FAs profile of different agri-food byproducts, namely grape pomace, grape stems, grape bunches, white less, red lees, BSG, carrot, and potato peels using chromatographic and spectrometric approaches, as a strategy to evaluate its potential application for food-based matrices enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…The content in TSP of the WL was within the range (17.3–40.9 g/kg DM) reported by Zhijing et al [ 28 ] for red WL, although others have reported much greater values [ 26 ]. Chemical composition of WL can be influenced by many factors such as environmental conditions, grape variety and characteristics of the wine making process [ 29 , 30 ]. Moreover, the organic cultivation of the WL used in our study could have contributed to their low CP content, as organic crops usually have lower CP compared with conventional cultivation due to restrictions in N fertilization [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Este material se encuentra en una parcela, situada en el término municipal de San José del Valle (Cádiz, España) a 150 sobre el nivel del mar. Se llevó a cabo una identificación genética mediante marcadores moleculares tipo microsatélites para comprobar el genotipo de las diferentes variedades y variantes somáticas sujetas a estudio, siguiendo la metodología empleada por Sancho-Galán et al, [28][29]. El análisis morfológico de los distintos cultivares se llevó a cabo mediante el empleo de una lista de descriptores morfológicos seleccionados del Cógido de Descriptores de la Organización Internacional de la Vid y el Vino (OIV) [30].…”
Section: Materials Y Métodosunclassified
“…La identificación genética permitió corroborar el genotipo de estas variedades de vid locales o autóctonas y las variantes somáticas, comparándose el genotipo obtenido con los publicados en la base de datos del Catálogo Internacional de variedades de vid (VIVC: www.vivc.de) [28][29]. En las Tablas 1 y 2 se destacan las diferencias encontradas para las distintas variedades autóctonas y variantes somáticas de la variedad Palomino Fino.…”
Section: Análisis Morfológico De Variedades De Vid Locales O Autócton...unclassified